Unveiling Cs-adsorption mechanism of Prussian blue analogs: Cs+-percolation via vacancies to complete dehydrated state. Issue 61 (10th October 2018) - Takahashi, Akira; Tanaka, Hisashi; Minami, Kimitaka; Noda, Keiko; Ishizaki, Manabu; Kurihara, Masato; Ogawa, Hiroshi; Kawamoto, Tohru
Abstract : Cs + adsorption selectivity caused by hydration energy and percolation theory to evaluate the ion-exchangeable site ratio. Abstract : Metal hexacyanoferrates (MHCF) or Prussian blue analogs are excellent Cs + -adsorbents used for radioactive Cs-decontamination. However, the adsorption mechanism is controversial. To clarify the issue, we quantitatively investigated the Cs-adsorption behaviors of potassium copper hexacyanoferrate (KCuHCF) and A y Cu[Fe(CN)6 ]1− x · z H2 O. To obtain samples having homogeneous chemical composition and particle size, flow systems were used for both synthesis and purification. After sufficient rinsing with water, the range of x stable in aqueous solution in time appropriate for Cs-adsorption was 0.25 < x < 0.50. The relations y = 4 − 2 x and z = 10 x were also found independent of x, indicating complete dehydration of K + in the crystal. We concluded that the excellent Cs-selectivity of MHCF was not due to difference in free energy of the adsorbed state between K + and Cs + but because of the hydrated state in aqueous solution. We also found that the guiding principle for determining the maximum capacity depended on the chemical composition. In particular, for the range 0.25 < x < 0.35, we propose a new model to understand the suppression of the maximum capacity. In our model, we hypothesize that Cs + could migrate in the crystal only through [Fe(CN)6 ] 4− vacancies. The model reproduced the observed maximum capacity without fitting parameters. The model would also be applicable to other MHCFs, e.g. a little adsorption by soluble Prussian blue. The ion exchange between Cs + and H + occurred only when the implemented K + was small.